The financial crisis and Federal Reserve policy - Thomas, Lloyd Brewster (2011)
This new book will provide an extensive analysis of the role of the Federal Reserve in contributing to the crisis through its low interest-rate policy during 2002-2006, and in dealing with the crisis under Bernanke with his aggressive and innovative policies implemented in the wake of the Lehman collapse in September 2008.
Includes bibliographical references (pages 251-253) and index.
oif 16/09/14
Loan
Keywords: Global Financial Crisis, 2008-2009.; Financial crises; Monetary policy